DIAGNOSTIC ACCURACY OF ULTRASOUND IN DETECTION OF SYMPTOMATIC URETERIC CALCULI TAKING NON CONTRAST CT SCAN AS A GOLD STANDARD. : J Peop Univ Med Health Sci. 2025:15(2),13-20. http://doi.org/10.46536/jpumhs/2025/15.02.619 - Mansab Ali1, Syed Muhammad Yousaf Farooq2 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Urolithiasis is defined as the presence of calculi in the urinary tract. Multiple studies have shown that urinary tract stones are one of the most common incidental findings in medical imaging. These stones are potentially dangerous and can cause severe impairment to renal function if they remain undiagnosed for a long time. To evaluate the diagnostic accuracy of ultrasound in the detection of symptomatic ureteric calculi taking a non-contrast CT scan as a gold standard. METHODOLOGY: A cross sectional analytical study was conducted in 9 months at Department of Diagnostic Radiology D.H.Q Hospital Jhang, Pakistan. 100 patients were selected with Consecutive sampling technique, Age of 18 to 80 years, both genders, Patients who presented with urinary symptoms and were suspected to have a urinary stone patients were included in this study. Patients with renal masses, previous renal surgeries, renal transplants and end-stage renal disease and pregnant females and patients not willing to participate in the study were excluded. RESULTS: The sensitivity of Ultrasound was 90.91%, specificity was 100%, Predictive positive value was 100% and predictive negative value was 10% so the diagnostic accuracy was 91%. CONCLUSION: Study concluded that the sensitivity of USG for diagnosis of ureteric calculi was high.